From ivory tower to inclusion: Stakeholders’ experiences of community engagement in Australian autism research - den Houting, Jacquiline; Higgins, Julianne; Isaacs, Kathy; Mahony, Joanne; Pellicano, Elizabeth (Frontiers in Psychology, 2022)
Autistic people, and other community stakeholders, are gaining increasing recognition as valuable contributors to autism research, resulting in a growing corpus of participatory autism research. Yet, we know little about the ways in which stakeholders practise and experience community engagement in autism research. In this study, we interviewed 20 stakeholders (academics, autistic people, family members/carers, research students, and service providers) regarding their experiences of community engagement in Australian autism research. Through reflexive thematic analysis of interview data, we generated four themes. First, our participants perceived academia as an “ivory tower”, disconnected from community members’ lives and priorities. Second, our participants identified that different stakeholders tended to hold different roles within their research projects: academics typically retained power and control, while community members’ roles tended towards tokenism. Third, our participants spoke of the need to “bridge the gap” between academia and the community, highlighting communication, accessibility, and planning as key to conducting effective participatory research. Lastly, participants emphasised the changing nature of autism research, describing participatory research as “the way of the future”. Our findings reflect both the progress achieved to date, and the challenges that lie ahead, as the field advances towards genuine co-production of autism research.